Metabolic and microbial responses of Ceratitis capitata to essential oil-based nano-emulsions: Implications for pest management - Modafferi, Antonino; Urbaneja, Alberto; Aure, C.M.; Giunti, G.; Martínez-Sañudo, I.; Ienco, A.; Campolo, O.; Palmeri, V.; Pérez-Hedo, M. (Elsevier, 2025)
Essential oils (EOs) are a promising alternative to conventional pesticides, but some challenges like high volatility, poor water solubility, and rapid degradation limit their use in Integrated Pest Management (IPM). To overcome these limitations, this study aimed to develop garlic, eucalyptus, and clove EO-based nano-emulsions (EO-NEs) in a bait treatment format through the high-pressure microfluidization technique and investigated the biological activities against Ceratitis capitata. In addition, the adverse effects of the most promising nanoemulsion were evaluated towards a non-target parasitoid Anagaspis daci. The garlic nano-emulsion (garlic-NE) with estimated LD50 and LD90 of 0.96 and 2.18 % of EO showed high insecticidal activity against C. capitata. Instead, eucalyptus and clove nano-emulsions exibhited low and mediuam mortality rates respectively. However, garlic-NE exhibited high toxicity (100 % mortality) towards the non-target parasitoid A. daci. We analyzed the expression of 14 genes involved in detoxification pathways to investigate the mechanisms underlying garlic-NE toxicity. Our results showed that garlic-NE triggered a strong metabolic detoxification response, leading to the upregulation of cytochrome P450 monooxygenases (CYPs), glutathione S-transferases (GSTs), and alcohol dehydrogenase (Adh). Furthermore, garlic-NE induced significant shifts in the gut microbiota composition of C. capitata 72 h after the treatment, disrupting its microbial homeostasis. This dual effect—metabolic stress combined with microbiota disruption—suggests that garlic-NE exerts its insecticidal action through a multifaceted mode of action rather than direct neurotoxicity, potentially reducing the risk of resistance development. Overall, this study highlights the potential of EO-based nano-formulations as alternatives to conventional pesticides.